Offices of Tenebrae? Castellanos and Glantz versus the national “machismo” of the “culturalismo mexicanista” (Ogigia. Revista Electrónica de Estudios Hispánicos, 2019)
Taking as starting point the interweaving between nationalism and gender, this article wants to resize the writings of Rosario Castellanos and Margo Glantz, as two instances that disrupt, deny or deconstruct the Mexican “machista” historiography. This would have been covered by the “inteligencia de lo mexicano”, Samuel Ramos and Octavio Paz, mainly. In this regard, the intention of the text is not the proposal of a feminist reading of nationalism, although the insistence in remarkable female voices versus the “machismo” of what we called "culturalismo mexicanista".
Keywords: Gender; Nationalism; Feminine writing; Mexican; Rosario Castellanos; Mago Glantz; inteligencia de lo mexicano; Samuel Ramos; Octavio Paz